HETEROSIS AND COMBINING ABILITY STUDIES FOR YIELD AND YIELD ATTRIBUTING TRAITS IN BRINJAL (SOLANUM MELONGENA L.) - RAGHVENDRA DUBEY; ARPITA DAS; M. D. OJHA; BHOLANATH SAHA; ASHISH RANJAN; P. K. SINGH (The Bioscan, 2014)
A study was conducted in brinjal to identify superior parental combination and to estimate the magnitude of heterosis for yield and its eleven yield components. 48 F1 hybrids generated following line x tester mating design comprising of 12 lines and 4 testers and were evaluated in a randomized block design with three replications at Vegetable Farm of Narendra Deva University of Agriculture and Technology, Kumarganj, Faizabad (Uttar Pradesh). The analysis revealed that Sel-4 was the best general combiner among the lines and IC-90099 was the best general combiner among the testers. There was high heterosis response in most of the hybrids which supports the role of non-additive gene effects. Among the crosses, DBL-24 x PPC showed high sca effects for yield although the parents were poor general combiners. The maximum heterosis for total yield per plant over better parent was exhibited by the cross KS-314 x IC-90099 (94.72%) followed by KS-314 x PPC (85.10%). Indirect selection for traits such as plant height, long and medium styled flowers per clusters, fruits per plant, fruit length, fruit diameter and primary branches per plant could be done in order to achieve higher yield through heterosis breeding. The present study reveals good scope for isolation of pure lines from the progenies of heterotic F1s as well as commercial exploitation of heterosis in brinjal.